Prevalence and associations of nonglaucomatous optic nerve atrophy in high myopia: original article: the ural eye and medical study - Bikbov, Mukharram; Iakupova, Ellina M.; Gilmanshin, Timur R.; Bikbova, Guzel M.; Kazakbaeva, Gyulli M.; Panda-Jonas, Songhomitra; Gilemzianova, Leisan I.; Jonas, Jost B. (Ophthalmology, 2023)
Purpose - To assess the prevalence of nonglaucomatous optic nerve atrophy (NGOA) in highly myopic individuals. - Design - Population-based study. - Participants - The Ural Eye and Medical Study included 5899 (80.5%) of 7328 eligible individuals (80.5%). - Methods - Nonglaucomatous optic nerve atrophy, graded into 5 arbitrary stages, was characterized by decreased visibility of the retinal nerve fiber layer (RNFL) on photographs, neuroretinal rim pallor, abnormally thin retinal arteriole diameter, and abnormally thin peripapillary RNFL as measured by OCT. - Main Outcome Measures - Nonglaucomatous optic nerve atrophy prevalence and degree. - Results - Of 5709 participants (96.9%) with axial length measurements, 130 individuals (2.3%) were highly myopic, of whom 116 individuals (89.2%; age, 57.8 ± 11.1 years; axial length, 27.0 ± 1.2 mm) had available fundus photographs and OCT images and were included into the study. Nonglaucomatous optic nerve atrophy prevalence was 34/116 individuals (29.3%; 95% confidence interval [CI], 21.0-38.0), and mean NGOA degree in eyes with NGOA was 1.7 ± 1.0 arbitrary units. Higher NGOA degree correlated (multivariable analysis; regression coefficient, r2 = 0.59) with longer axial length (β, 0.22; P = 0.007), wider temporal parapapillary γ zone width (β, 0.50; P < 0.001), higher prevalence of diabetes (β, 0.20; P = 0.005), and higher systolic blood pressure (β, 0.15; P = 0.03). Higher NGOA prevalence was associated with longer axial length (odds ratio [OR], 7.45; 95% CI, 2.15-25.7), wider temporal parapapillary γ zone (OR, 6.98; 95% CI, 2.61-18.7), and higher systolic blood pressure (OR, 1.05; 95% CI, 1.01-1.10). - Conclusions - In this ethnically mixed population from Russia with an age of 40 years or more, high axial myopia showed a relatively high prevalence of NGOA, increasing with longer axial length and wider temporal parapapillary γ zone. For each 1 mm of axial elongation and γ zone widening, the odds for NGOA increased 7.45-fold and 6.98-fold, respectively. The axial elongation-associated and γ zone-related increase in the distance between the retinal ganglion cells and the optic disc may lead to a lengthening and stretching of the retinal ganglion cell axons and may be of importance pathogenetically. In highly myopic eyes, NGOA may be a reason for visual field and central visual acuity loss, unexplainable by myopic macular pathologic features. - Financial Disclosure(s) - Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.
Online verfügbar: 17. Juli 2023, Artikelversion: 19. Oktober 2023
Gesehen am 18.06.2024